The Transformative Learning Potential in the Hybrid Space Between Technology and Intercultural Encounters. (July 2022) - Jørgensen, Mette; Mason, Amanda; Pedersen, Rikke; Harrison, Roger
As many higher education institutions strive to internationalize and develop graduates as global citizens, new technologies are supposed to be creating opportunities for geographically dispersed students to meet and develop intercultural skills. We argue, however, that there is scant evidence that these opportunities are being fully exploited. In this article, we explore some of the reasons for this by using the lens of "third space" theories to interpret data from a preliminary study of an international virtual exchange project. We found that although the project afforded some scope for critical intercultural learning, this was limited by two key factors related to the second space of the traditional classroom: the skills and attitudes of the lecturers and asymmetries in project goals. We conclude by arguing that unless higher education institutions provide more fertile conditions for projects like these, further opportunities for intercultural learning will be missed.